A tunable source of coherent terahertz radiation driven by the microbunched electron beam - Zhang, H; Konoplev, I; Doucas, G (IOP Publishing, 2019)
The studies of coherent terahertz (THz) tunable Smith–Purcell radiation source driven by the microbunched electron beam are presented. We discuss the conceptual design of a high power and broadly tunable THz radiation source capable of bridging the THz technological gap. The results of the numerical and analytical studies using different software packages, models and approaches are shown and good agreement between the results is demonstrated. The spectra of the coherent Smith–Purcell radiation (cSPr) excited by a single bunch and a train of microbunches are compared and the excitation of the harmonics of cSPr is discussed. It is shown that varying the distance between microbunches the power and the frequency of the output cSPr can be controlled.